Advances in agronomy. - Sparks, Donald L.; Arrouays, D. (Dominique) (Advances in Agronomy., 2014)
Advances in Agronomy continues to be recognized as a leading reference and a first-rate source for the latest research in agronomy. As always, the subjects covered are varied and exemplary of the myriad of subject matter dealt with by this long-running serial.